Prevalence of metabolic syndrome in Nepal: A systematic review of all published studies - Rana, Raju; Kamath, Shobha U; Shastri, B Ananthakrishna; Umakanth, Shashikiran; Maiya, G Arun; Kamath, Ullas; Rao S, Raghavendra; Adhikari, Purnima (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Metabolic syndrome (MetS) encompasses a cluster of medical conditions that significantly increase the risk of type 2 diabetes mellitus (T2DM), cardiovascular disease (CVD), cancer, and stroke. The global prevalence of MetS is rising, with a notable increase across South Asian countries. Multiple studies from diverse regions of Nepal, examining both general and clinical populations, have documented high MetS prevalence rates. This systematic review aims to determine the comprehensive prevalence of MetS in Nepal.Methods: We conducted systematic searches across PubMed, Web of Science, Scopus, and EMBASE databases. Our review included all studies reporting MetS prevalence in Nepal among individuals aged 15 years and older, regardless of the study setting. We calculated the weighted mean prevalence and assessed study quality using the Joanna Briggs Institute (JBI) critical appraisal tool for prevalence studies.Results: In the general population (n=6,065; males:34%, females:66%), the weighted mean prevalence of MetS ranged from 17.11% to 18.41%, varying by diagnostic criteria. MetS prevalence was higher among females (females:17.73-20.78%: males: 14.93-16.64%), older adults, and individuals with lower educational attainment. Among populations with existing medical conditions, MetS prevalence was highest in patients with T2DM (90.36%, n=1710; males:54%, females:46%) and lowest in those with Psoriasis (20.83%, n=72).Conclusions: Our findings demonstrate the substantial prevalence of MetS; interpretation must consider the variability in diagnostic criteria across studies and the predominant focus on major urban centres. Authorities should focus on interventions addressing modifiable risk factors such as alcohol consumption, smoking, and physical inactivity to reduce the overall disease burden.